2020
DOI: 10.1021/acs.inorgchem.0c00181
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Driven Hexagonal-to-Monoclinic Transition in BiPO4: An In-Depth Experimental Investigation and First-Principles Study

Abstract: Present theoretical and experimental work provides an in-depth understanding of the morphological, structural, electronic, and optical properties of hexagonal and monoclinic polymorphs of BiPO 4 . Herein, we demonstrate how microwave irradiation induces the transformation of the hexagonal to a monoclinic phase one in a short period of time and thus, the photocatalytic performance of BiPO 4 . To complement and rationalize the experimental results, first-principle calculations have been performed within the fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…The photocatalysts were irradiated under ultraviolet light, followed by UV-vis analysis to estimate the concentration of remaining RhB. It could be observed that the characteristic absorption band of RhB (at 554 nm) decreases as a result of the gradual de-ethylation of the functional groups N,N'-diethylammonium, causing the color to change from pink to transparent [63].…”
Section: Photocatalytic Degradation Of Rhodamine-b and 4-nitrophenolmentioning
confidence: 99%
“…The photocatalysts were irradiated under ultraviolet light, followed by UV-vis analysis to estimate the concentration of remaining RhB. It could be observed that the characteristic absorption band of RhB (at 554 nm) decreases as a result of the gradual de-ethylation of the functional groups N,N'-diethylammonium, causing the color to change from pink to transparent [63].…”
Section: Photocatalytic Degradation Of Rhodamine-b and 4-nitrophenolmentioning
confidence: 99%
“…The phase transition of BiPO 4 from low-or-high temperature monoclinic phase (LTMP-or-HTMP) to hexagonal phase (HP) occurs through continuously doping trivalent Ln 3+ /Eu 3+ ions. Their different samples composition proportions i.e., 6:1 (half HP + half LTMP), 1:1 (more HP + less LTMP), 0.5:1 (pure HP), 7:1 (pure LTMP) and 20:1 (less HP + more LTMP), exhibits different phonon detuning [11]. Different crystals structure determines different lattice vibration frequencies of phase transition phonon.…”
Section: Introductionmentioning
confidence: 99%
“…V O present in the clusters can become V O • and V O •• depending on how photogenerated e – –h + pairs shift on the CeO 2 surface by cluster–cluster charge transfer (Figure e; steps I and II). According to Tello et al, V O • /V O •• formation in the clusters favors the processes that lead to H 2 O oxidation/O 2 reduction (Figure e; steps IV and V), resulting in the formation of ·OH and ·O 2 – radicals. After the redox processes, the clusters regenerate, continuing the oxidation processes (Figure e; steps III–V).…”
Section: Resultsmentioning
confidence: 99%